2021
DOI: 10.1093/toxsci/kfab039
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Transcriptomic Analysis of Human Primary Hepatocyte Spheroids Exposed to Per- and Polyfluoroalkyl Substances as a Platform for Relative Potency Characterization

Abstract: Per- and poly-fluoroalkyl substances (PFAS) are widely found in the environment because of their extensive use and persistence. Although several PFAS are well studied, most lack toxicity data to inform human health hazard and risk assessment. This study focussed on four model PFAS: perfluorooctanoic acid (PFOA; 8 carbon), perfluorobutane sulfonate (PFBS; 4 carbon), perfluorooctane sulfonate (PFOS; 8 carbon), and perfluorodecane sulfonate (PFDS; 10 carbon). Human primary liver cell spheroids (pooled from 10 don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 57 publications
7
84
0
Order By: Relevance
“…Gene profiling was conducted using Affymetrix 430_2 microarrays. In GSE144775, the human primary hepatocytes and Kupffer cells from 10 different human liver donors were cultured in vitro . The cells were exposed to PFOS for 1, 4, 10, or 14 days at doses of 0, 0.02, 0.1, 0.2, 1, 2, 10, and 20 μM.…”
Section: Methodsmentioning
confidence: 99%
“…Gene profiling was conducted using Affymetrix 430_2 microarrays. In GSE144775, the human primary hepatocytes and Kupffer cells from 10 different human liver donors were cultured in vitro . The cells were exposed to PFOS for 1, 4, 10, or 14 days at doses of 0, 0.02, 0.1, 0.2, 1, 2, 10, and 20 μM.…”
Section: Methodsmentioning
confidence: 99%
“…PFOS increased the expression of PPARα target genes Acox1 and CYP4A10 in mouse liver, thereby activating PPARα and causing pathological changes in the liver tissue [ 136 ]. Recently, in a study using a primary human hepatocyte spheroid model, PPARα activity was found to be increased by PFAS exposure in human liver spheroids, particularly by PFOS exposure [ 137 ]. Previous studies have shown that PFOS can differentially activate PPARα in mice and humans [ 138 , 139 ].…”
Section: Signaling Pathways Associated With Hepatotoxic Damage Caused...mentioning
confidence: 99%
“…The use of well‐characterized cell lines offers a wide array of possibilities for manipulating experimental variables to obtain a multitude of endpoints in a timely manner. The utility of screening methods employing HTS methods has already been demonstrated for PFAS chemicals (Reardon et al, 2020; Rowan‐Carroll et al, 2021; Singh & Hsieh, 2021). While not inclusive of all assays, endpoints, and cell types, Table 2 provides some examples of approaches that can be and are being used for assessing the human health effects of short‐chain PFAS.…”
Section: Advantages and Limitations Of In Vitro Methodsmentioning
confidence: 99%